2006
DOI: 10.1152/japplphysiol.01066.2005
|View full text |Cite
|
Sign up to set email alerts
|

Contractile dysfunction and altered metabolic profile of the aging rat thyroarytenoid muscle

Abstract: The larynx and its muscles are important for ventilation, coughing, sneezing, swallowing, Valsalva's maneuver, and phonation. Because of their functional demands, the intrinsic laryngeal muscles have a unique phenotype: very small and fast fibers with high mitochondrial content. How aging affects their function is largely unknown. In this study, we tested the hypothesis that an intrinsic laryngeal muscle (thyroarytenoid muscle, a vocal fold adductor) would become weaker, slower, and fatigable with age. Muscles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 37 publications
4
56
0
Order By: Relevance
“…In animal models, these modifications are of sufficient magnitude to alter the muscle's contractile properties toward a slower, weaker, and less fatigue-resistant profile. 71 Likely contributors to the structural and functional changes include myelinization alterations within the RLN and SLN, reduced number of axonal terminals, decreased vascular support, systemic hormonal changes, and stochastic damage. [110][111][112][113][114]133,142,[146][147][148]183,184 The above discussion has also highlighted the distinctive nature of the TA muscle.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In animal models, these modifications are of sufficient magnitude to alter the muscle's contractile properties toward a slower, weaker, and less fatigue-resistant profile. 71 Likely contributors to the structural and functional changes include myelinization alterations within the RLN and SLN, reduced number of axonal terminals, decreased vascular support, systemic hormonal changes, and stochastic damage. [110][111][112][113][114]133,142,[146][147][148]183,184 The above discussion has also highlighted the distinctive nature of the TA muscle.…”
Section: Discussionmentioning
confidence: 99%
“…The question remains as to whether the sarcopenic features of limb skeletal muscle can be generalized to other muscles throughout the body. Some have argued that muscles of the head and neck are unique in their morphology as well as in their response to aging 70,71 and that these muscles should, therefore, be considered separately during studies of age-related decline. Below is a review of the morphological changes observed with age and the primary influences or domains associated with these changes.…”
Section: Age-related Changementioning
confidence: 99%
See 2 more Smart Citations
“…In prior studies, tongue twitch contraction times for evoked retrusive tongue actions was prolonged in old rats when compared with young, while there was no difference in twitch half-decay times [15]. Conversely, in rat larynx (thyroarytenoid muscle), halfdecay time was prolonged in old animals without a concurrent extension of twitch contraction time [16]. Accordingly, our goal was to examine these temporal elements for evoked protrusive tongue actions in old vs. young rat tongue.…”
Section: Hypoglossal Nerve Stimulation and Muscle Contraction Recordingsmentioning
confidence: 95%